A Risk Assessment Methodology and Excel Tool for Acquisition Programs - Mayer, Lauren A.; Arena, Mark V.; McMahon, Michael E. (RAND Corporation, 2023)
Implementing risk management principles for large defense acquisition programs is a priority for the U.S. defense acquisition community. To assist decisionmakers responsible for identifying major weapons programs’ risks, RAND developed a methodology and accompanying Excel risk tool (the “Assessor Tool”). It offers an approach to the evaluation of system integration risk for assessors such as Office of the Secretary of Defense staff.